Charismatic speech features in robot instructions enhance team creativity - Fucinato, Karen; Niebuhr, Oliver; Nørskov, Sladjana; Fischer, Kerstin (Frontiers in Communication, 2023)
This study examines whether a social robot can enable team creativity and increase team performance depending on its speaking style. The aim is to provide insight into human teams’ creativity and performance when exposed to different ways of speaking by a social robot, that is, when the robotic creativity facilitator is using different acoustic-prosodic features. In one condition, participants received their instructions from the robot in a “charismatic” speaking style, in the other, the robot used a less engaging way of speaking. The results show that when the robot’s speech is based on charismatic speech characteristics, it is significantly better at enhancing team creativity and performance than when its speech uses fewer charismatic speech characteristics. The robot’s speaking style thus influences its effectiveness as team creativity facilitator.